Biochar-Materials for Remediation on Swamplands: Mechanisms and Effectiveness - Annisa, Wahida; mukhlis, mukhlis; Hairani, Anna (Jurnal Sumberdaya Lahan, 2021)
Abstract. The purpose of this paper is to synthesize all research results qualitatively to explore the potential of biochar as a remediation agent in swamps, including its mechanism, and effectiveness. The soil in swampland is characterized by the presence of pyrite (FeS2) which results in high acidity (soil pH <3.5). The reduction process in swamps produces high amounts of ferrous iron (Fe2+) which is then released into the environment. The mechanism of iron (Fe) poisoning is indicated by the inhibition of nutrient uptake because the roots are covered with iron. This disturbes the root function as a nutrient absorber. Recent research shows that biochar could be used as an approach to reduce soil pollution in swamps through metal immobilization processes. This review paper uses a qualitative method with meta-aggregation approach based on the Francis-Baldesari method (2006). Principally, the soil remediation mechanism using biochar does not remove metals but accumulate them into hydroxide or carbonate deposits with the help of existing microorganisms. Provision of rice husk Biochar can increase the pH value reaching ≥5.0 and grain yield by 20% in intensively cultivated tidal swamps. Increasing the pH value of the soil will supports the formation of Fe hydroxide deposits which are accumulated on rice roots. Abstrak. Tujuan penulisan paper ini adalah mensintesis seluruh hasil penelitian secara kualitatif untuk menggali potensi biochar sebagai bahan remediasi pada lahan rawa meliputi mekanisme, dan efektivitasnya. Tanah di lahan ini dicirikan oleh keberadaan pirit (FeS2) yang menghasilkan keasaman tinggi (pH tanah <3,5). Proses reduksi di lahan rawa menghasilkan besi ferro (Fe2+) dalam jumlah tinggi dan dilepaskan ke lingkungan. Mekanisme keracunan besi (Fe) ditunjukkan dengan terhambatnya serapan hara karena perakaran diselimuti oleh besi sehingga fungsi akar sebagai penyerap unsur hara terganggu. Penelitian terbaru menunjukkan bahwa pemanfaatan biochar sebagai salah satu pendekatan untuk mengurangi pencemaran tanah di lahan rawa melalui proses immobilisasi logam. Paper review ini menggunakan metode kualitatif berdasarkan metode Francis-Baldesari (2006) dengan pendekatan metaagregasi (meta-aggregation). Mekanisme remediasi tanah menggunakan biochar prinsipnya tidak menghilangkan logam tetapi mengakumulasinya menjadi endapan hidroksida maupun karbonat dengan bantuan mikroorganisme yang ada. Pemberian Biochar sekam padi dapat meningkatkan nilai pH mencapai ≥5,0 dan hasil gabah sebesar 20% di lahan rawa pasang surut yang intensif dibudidayakan. Peningkatan nilai pH tanah mendukung pembentukan endapan hidroksida Fe yang diendapkan pada akar padi.